EVALUATION OF THE DIPLOMA ASSOCIATE CERTIFICATE IMPLEMENTATION PROGRAM: A STUDY AT A UNIVERSITY IN THE CITY OF BEKASI - Fa’uzobihi, Fa’uzobihi; Suseno, Muchlas; Supriyati, Yetti (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The implementation of the evaluation is to provide an understanding of the objectives of a policy, how it is implemented, and what impacts are obtained. Related research on the SKPI program carried out by universities in the Bekasi city area by conducting an evaluation using a combination of the CIPP and Kirkpatrik models which aims to determine the background, input, process, product and impact of the implementation of the program. This study uses a mixed method research design with the Explanatory Sequential Mixed Methods approach. The results of this study indicate that the implementation of the SKPI program received a very positive assessment and was considered to have a significant impact on improving the quality of graduates, preparing them for the global job market, and supporting the recognition of graduates at the national level. This program is also considered to be able to provide direct benefits in helping graduates get jobs that match their expertise. This reflects the importance of SKPI in increasing the relevance of education to industry needs and developing graduate competencies.